Time to Diagnosis and Treatment with Palliative Radiotherapy among Inuit Patients with Cancer from the Arctic Territory of Nunavut, Canada. Issue 1 (January 2020) - Chan, J.; Linden, K.; McGrath, C.; Renaud, J.; Doering, P.; MacDonald, S.; Gaudet, M.; Pantarotto, J.R.; Asmis, T.; Slotman, B.; Dennis, K.
Abstract: Aims: The cancer burden among Circumpolar Inuit is high. Palliative radiotherapy is a mainstay treatment for controlling symptoms of advanced cancers, but Inuit are required to travel far distances to access this service. Access to palliative radiotherapy and time away from home communities have not been explored among this population. We sought to describe the time intervals from symptom onset to the start of palliative radiotherapy among Canadian Inuit patients treated at The Ottawa Hospital (TOH). Materials and methods: A retrospective review of Inuit patients from Nunavut treated with radiotherapy between 2005 and 2014 at TOH. Results: Of a total of 152 radiotherapy patients, 88 (58%) were treated palliatively. Of these, 61 (70%) had stage IV disease at diagnosis and 63 (72%) had lung cancer. The median time from referral for specialist care to the patient's first flight to Ottawa was 4 days (range 0–97). The median length of treatment was 7 days (range 0–27), but patients spent a median of 64.5 days (range 14–633) in Ottawa. The median survival from the date of pathological diagnosis was 5.2 months. Conclusions: Most Inuit radiotherapy patients at TOH were treated palliatively. Patients were brought from Nunavut relatively quickly for specialist care, which is encouraging. However, patients spent over 2 months away from home, in the context of a median survival of less than 6 months. Opportunities for improvement include both provider and system-level changes, which may be applicable to other Circumpolar Inuit regions across Europe and North America. Highlights: Nearly 60% of Inuit radiotherapy patients from Nunavut were treated palliatively. A high proportion had stage IV disease at diagnosis (70%) and lung cancer (72%). Median time from referral for work-up to flight to referral hospital was 4 days. Patients spent a median of 64.5 days away from home for work-up and treatment. Survival was poor, with a median survival of 5.2 months from date of biopsy.